Penerapan Metode Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) dalam Pemilihan Wiraniaga Terbaik - Asep Toyib Hidayat; Nelly Khairani Daulay; Mesran Mesran (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
A salesperson is someone who makes direct sales to consumers. Salespeople are the most important people in marketing the company's products. In this study, the aim is to select the best salespeople who can be compensated for the results of their performance. The method used in selecting the best salesman uses Multi-Objective Optimization on The Basis of Ratio Analysis (MOORA) contained in the decision support system (DSS). The results of the study on 15 salespeople obtained the best sales results with a value of 0.28.